To factor the polynomial \(13x^{11} - 117x^3\) completely, we can start by factoring out the greatest common factor (GCF).
-
First, we can factor out \(13x^3\): \[ 13x^{11} - 117x^3 = 13x^3(x^{8} - 9) \]
-
Now, we will focus on factoring \(x^{8} - 9\). This expression is a difference of squares: \[ x^{8} - 9 = (x^{4})^2 - 3^2 = (x^{4} - 3)(x^{4} + 3) \]
-
Putting it all together, we have: \[ 13x^{11} - 117x^3 = 13x^3(x^{4} - 3)(x^{4} + 3) \]
Thus, the complete factorization of the polynomial is: \[ \boxed{13x^3(x^{4} - 3)(x^{4} + 3)} \]